PENGARUH BUDAYA ORGANISASI DAN PENGAMBILAN KEPUTUSAN TERHADAP KOMITMEN ORGANISASI DI SEKOLAH MENENGAH KEJURUAN NEGERI 1 BATANG HARI - Nurlaila Winda Septiana; Kholid Ansori (Kampus Akademik Publiser, 2026)
This study aims to determine the influence of organizational culture and decision-making on organizational commitment at State Vocational High School 1 Batang Hari. This study employed a quantitative research method with a survey design using a questionnaire as the instrument for data collection. The data were analyzed using multiple regression analysis with the assistance of SPSS software version 20.0. Quantitative research is categorized as descriptive research, which describes a phenomenon using statistical data or numerical analysis to obtain answers to the formulated research questions. The population in this study consisted of educators and administrative staff of State Vocational High School 1 Batang Hari, comprising 48 educators and 16 administrative staff. The hypothesis testing applied simple correlation analysis between Ha and Ho. Based on the research findings, it was revealed that organizational culture has a significant influence on organizational commitment, indicated by *tcount > ttable* or *2.108 > 1.669*. Decision-making also has a significant influence on organizational commitment, with *tcount > ttable* or *5.3899 > 1.669*. The results of the regression coefficient test show that organizational culture and decision-making jointly influence organizational commitment at State Vocational High School 1 Batang Hari. The contribution percentage of the independent variable X1 (Organizational Culture) is 0.132, and X2 (Decision-Making) is 0.321 toward the dependent variable Y (Organizational Commitment), while the remaining 0.012 is affected or explained by other variables not examined in this study.The conclusion of this research is that the level of organizational commitment at State Vocational High School 1 Batang Hari is influenced by the variables of organizational culture and decision-making.